Volcanoes of Auckland: The Essential Guide - Campbell, Hamish (New Zealand Science Review, 2011)
​Essential? A guide to a bunch of volcanoes in Auckland? I dashed home with this book safely stowed in my briefcase, feeling dubious. To be essential means affecting the essence of something – that which defines its very being, that which makes it and is perforce important. It can also mean absolutely necessary. I tentatively dipped into the book over my usual refreshing mid-afternoon cup of tea with the children safely stowed from another day at school. Such is my routine. I was gripped from the start and could not put it down. I read it all in two sittings – one in daylight the other in bed – and thus I found my only serious criticism of the book’s presentation. The pale grey font reserved for figure captions is best viewed in daylight and proved almost invisible in the soft light afforded by my bedside lamp. I imagine that publishing houses like Auckland University Press never sleep, so this failure probably remains to be market-tested. The same (i.e. never sleeping...) may be true of the senior author, who is very well-known in both New Zealand and international earth science. His ‘output’ is prodigious and always first class. He has carved a niche with his expertise in paleon-tology and micropaleontology in particular, specialising in the study of foraminifera, single-celled animals that live in water and are an incredibly important lower link in the food chain. He uses quantitative analysis of mainly fossil foraminifera but also modern species in solving geological and environmental problems. In so doing, he has become a natural science mega-star who has championed the worlds of conservation and environmental change